Graphene-Metal Nanostructures as Surface Enhanced Raman Scattering Substrates for Biosensing. (2017) - Rivolo, P.; Bianco, S.; Lamberti, A.; Chiadò, A.; Novara, C.; Giorgis, F.
Abstract: Multilayered structures composed by Single Layer Graphene (SLG), silver nanoparticles and polydimethylsiloxane membranes were used as SERS substrates for the analysis of porphyrins and hemoproteins (e.g. Myoglobin). The transfer process of SLG from its Cu growth substrate to the Ag-decorated polydimethylsiloxane membrane was optimized. A Limit of Detection (LOD) of 10 -8 M was found for ethanolic solutions of Rhodamine 6G and the efficient detection of porphyrins and Myoglobin, adsorbed on SLG surface, was achieved. This study evidenced the potentialities of plasmonic graphene-based chips for biosensing.